2016
DOI: 10.1097/aog.0000000000001655
|View full text |Cite
|
Sign up to set email alerts
|

Women's Sexual Function, Satisfaction, and Perceptions After Starting Long-Acting Reversible Contraceptives

Abstract: Objective To document how long-acting reversible contraception (LARC) affects women’s sexual outcomes. Methods In this prospective, observational cohort study, we enrolled new-start intrauterine device (IUD) and contraceptive implant users attending four family planning clinics. Data collection occurred at baseline, one month, and three months. Primary outcomes were the Female Sexual Function Index, New Sexual Satisfaction Scale, and perceived sexual effects of method (positive, negative, or none). Secondary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 26 publications
1
24
0
2
Order By: Relevance
“…Here, we focus on contraceptive preferences. Participants responded to the query, “How important are each of the following characteristics to you in deciding which birth control method to use?” Characteristics included: “it doesn't contain hormones,” “it is acceptable to my partner,” “it doesn't interrupt sex,” “it doesn't reduce my libido,” “it is in line with my religious beliefs,” “it is recommended by my friend(s),” “it is the most effective method,” “it doesn't have side effects” and “it is safe for me to use.” Response options were “not at all important,” “slightly important,” “quite important” and “extremely important.” The sexual-related preferences arose from prior qualitative [ 13 , 14 ], theoretical [ 15 ] and clinical pilot work [ 10 ] by members of this research team.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we focus on contraceptive preferences. Participants responded to the query, “How important are each of the following characteristics to you in deciding which birth control method to use?” Characteristics included: “it doesn't contain hormones,” “it is acceptable to my partner,” “it doesn't interrupt sex,” “it doesn't reduce my libido,” “it is in line with my religious beliefs,” “it is recommended by my friend(s),” “it is the most effective method,” “it doesn't have side effects” and “it is safe for me to use.” Response options were “not at all important,” “slightly important,” “quite important” and “extremely important.” The sexual-related preferences arose from prior qualitative [ 13 , 14 ], theoretical [ 15 ] and clinical pilot work [ 10 ] by members of this research team.…”
Section: Methodsmentioning
confidence: 99%
“…Growing research documents that patients have a variety of preferences beyond safety and efficacy that could influence method selection [ 8 , 9 ]. This team's earlier study of 188 intrauterine device (IUD) or implant users indicated that although methods' efficacy influenced contraceptive decision making, so did their potential sexual impacts [ 10 ]. When selecting their new method, these patients ranked factors of “doesn't reduce my libido” and “doesn't interrupt sex” just as highly as efficacy and more highly than all other criteria.…”
Section: Introductionmentioning
confidence: 99%
“…We previously published information about this patient population’s baseline characteristics and shorter-term sexual outcomes as measured by the FSFI-6, the NSSS, and subjective measures of impact of contraception on one’s sex life (Higgins et al, 2016). In the current paper, we share data from beyond the first three months of use, including the relationship between women’s sexual outcomes and contraceptive method continuation out to one year.…”
Section: Methodsmentioning
confidence: 99%
“…The original study was powered to detect differences in FSFI-6 scores between Cu IUD, LNG IUD, and ENG implant users. Published results of the power analyses appear elsewhere (Higgins et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation